A rare cause of small bowel obstruction which should always be considered. (November 2017) - Evans, William; Rate, Anthony
Abstract : Introduction: Appendicitis has been known to cause acute small bowel obstruction through mechanical and physiological interactions with the ileum. Here a 52 year old male, who, following 3 days of lower abdominal pain, bowels not having opened and vomiting was found on computed tomography (CT) scan to have a mechanical small bowel obstruction. This was operated on via lower midline laparotomy and adhesiolysis. An inflamed appendix was found to have wrapped itself around the terminal ileum causing a focal stricture. After appendectomy the patient was discharged 6 days later and made a full recovery. Case description: A 52 year old man with a past history of GORD, hypertension and peripheral vascular disease (with aorto-bifemoral bypass) was admitted onto our Surgical Triage Unit (STU) at 22:10 on a Thursday evening. He complained of a 3 day history of illness consisting of cramping lower abdominal pain, bowels not having opened and recurrent bilious vomiting. Results and Conclusions: An urgent CT scan reported "High grade small bowel obstruction, with change of calibre in the distal ileum. This may be secondary to adhesions (previous bilateral femoral bypass) or internal hernia. Incidentally, the appendix also looks inflamed. No perforation or intra-abdominal collections." At laparotomy, the appendix was inflamed with free pus in the peritoneal cavity and dilated small bowel loops in the vicinity. On closer inspection it could be seen that the inflamed appendix had wrapped itself around the terminal ileum stenosing its lumen and causing the small bowel obstruction. Take home message: Always consider a concurrent appendicitis in cases of small bowel obstruction Do not exclude an appendicitis in cases of left sided abdominal pain as was the case here If suspected consider performing computed tomography before proceeding to surgery The co-existence of these two pathologies may alter operative approach